2018
DOI: 10.1002/jez.b.22802
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oocyte mRNA localization patterns in sterlet Acipenser ruthenus and African clawed frog Xenopus laevis

Abstract: In oocytes, RNA localization has critical implications, as assembly of proteins in particular subcellular domains is crucial to embryo development. The distribution of mRNA molecules can identify and characterize localized transcripts. The goal of this study was to clarify the origin of primordial germ cells in the oocyte body plan and to reveal the generation of cell lineages by localized RNAs. The distribution of 12 selected mRNAs in sterlet Acipenser ruthenus oocytes was investigated by qPCR tomography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…show an increasing gradient toward the vegetal region. Contrary to the situation described in X. laevis, in the animal region of A. ruthenus the otx1, wnt11, and veg1 mRNAs are localized (Pocherniaieva et al, 2018).…”
Section: Asymmetry In Oocytescontrasting
confidence: 87%
See 1 more Smart Citation
“…show an increasing gradient toward the vegetal region. Contrary to the situation described in X. laevis, in the animal region of A. ruthenus the otx1, wnt11, and veg1 mRNAs are localized (Pocherniaieva et al, 2018).…”
Section: Asymmetry In Oocytescontrasting
confidence: 87%
“…In the ovulated oocytes of A. ruthenus , the distribution of mRNAs that encode determinants of the germplasm ( dnd, vasa , and ddx25 mRNAs) show an increasing gradient toward the vegetal region. Contrary to the situation described in X. laevis , in the animal region of A. ruthenus the otx1 , wnt11 , and veg1 mRNAs are localized (Pocherniaieva et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…Recently it has been shown that in A. ruthenus ovulated oocytes, the distribution of mRNAs dnd , vasa , and ddx25 coding for germplasm determinants is uneven and shows increasing gradient towards the vegetal pole (Pocherniaieva et al 2018). In this pole, the primordial germ cells (PGCs) develop (Ostaszewska and Dabrowski 2009; Saito et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly the endoderm of the A. ruthenus develops in the meridian area while the meso-and ectoderm layers shift towards the animal part compared to X. laevis. The vegetal part of A. ruthenus contains the primordial germ cell factors and also the yolk, which is used as an extra-embryonic tissue with nutritional function (Dettlaff et al 1993;Saito et al 2014;Pocherniaieva et al 2018). The D. rerio fate map closely resembles that of the A. ruthenus (Fig.…”
Section: Introductionmentioning
confidence: 99%